Post-Vaccination AI (Avian Influenza) Antibody Levels in Superior Native Chicken Balitnak (Kub Chicken) with Arab Chicken Aged 25 Days - Maratun Janah (Chalaza Journal of Animal Husbandry, 2022)
In Indonesia, native chickens are still in demand by the community. However, this type of chicken has low productivity compared to purebred chickens. At this time, there has been a type of native chicken that is Arab Chicken that has been widely developed in Indonesia because it has better endurance than other native chickens. In addition to Arabic chickens, there are also KUB chickens developed by the Bogor Livestock Research Institute to address the problem of low productivity of native chickens. But these two types of chickens remain susceptible to diseases, such as Avian Influenza (AI). To overcome this breeders conduct AI vaccinations using inactive vaccines. This study aims to find out the difference between post-vaccination antibodies between KUB chickens and Arab chickens. This research has been conducted from June to August 2018. The chickens used amounted to 40 chickens (20 KUB chickens and 20 Arab chickens). The chickens are kept from the age of one day and placed in two separate cages according to their breed. Intracardial blood sampling was pre-treatment (three days old) for the 40 chickens. At the age of four days, the chickens were injected with an inactive AI vaccine, and 21 days later blood sampling was again carried out (post-treatment). HI, tests are used to find out titer antibodies pre and post-treatment. The results of antibody titer readings were then analyzed using a t-test and Geometric Mean Titer test (GMT). T-test results showed that T value (6,364)T table (1,734), so the results of this study showed that the titer antibodies formed are different (P0.05). KUB chickens have higher antibody titers than Arab chickens.